The impact of initial public offerings on SMEs’ foreign investment decisions - Jiang, Guoliang Frank; Reuer, Jeffrey J.; Southam, Colette; Beamish, Paul W. (Journal of International Business Studies, 2022)
This study aims to bridge the research on the internationalization of small- and medium-sized enterprises (SMEs) with the literature on initial public offerings (IPOs). It investigates how IPOs affect SMEs’ foreign investment decisions as they internationalize. We argue that IPOs enable SMEs to engage in a period of accelerated foreign expansion, resulting in a wave-like pattern, as suggested by Håkanson and Kappen’s (J Int Bus Stud 48(9):1103–1113, 2017) ‘Casino model’ of internationalization. We also propose that there will be a post-IPO shift in SMEs entering less familiar locations and towards taking higher ownership stakes in new subsidiaries. We use a difference-in-differences design combined with coarsened exact matching to isolate the effects of IPOs. Our analysis of overseas investments by a matched sample of newly listed Japanese manufacturing SMEs and their private counterparts provides strong evidence that SMEs accelerate the pace of establishing new foreign subsidiaries after going public. The results also reveal nuanced changes in the location and ownership patterns in the post-IPO period. This study identifies the IPO as a significant antecedent to SME foreign expansion and offers a new explanation for intertemporal variance in the pace, direction, and commitment of the SME internationalization process.